1970
DOI: 10.1063/1.1673300
|View full text |Cite
|
Sign up to set email alerts
|

Transient Photoconductivity in Poly(N-vinylcarbazole)

Abstract: Transport of holes through thin films of poly(N-vinylcarbazole) was studied using transient photoconductivity techniques. The photogeneration depends on the electric field with quantum efficiency of generation approaching a value of 0.1 at an applied electric field of 108 V/m. The motion of carriers cannot be characterized by a drift mobility but can be fully represented by an “effective transit time” given by (Teff)−1 = (mτ0)−1exp(γE1/2 − ε0 / kT), where m = d / d0 (d being the thickness of the film and d0 a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(99 citation statements)
references
References 6 publications
5
94
0
Order By: Relevance
“…Experimental studies of the mobility in systems containing conjugated small molecules in an insulating polymer matrix, as a function of the molecule concentration, have revealed values of ␣ −1 around 0.1 nm. 10 The site densities in congated polymers such as OC 1 C 10 -PPV are of the order N t Ϸ 10 26 to 10 27 m −3 , corresponding to average nearest neighbor intersite distances around 1 nm. A representative value of the reduced site density is thus N t / ␣ 3 ϳ 10 −3 .…”
Section: Semianalytical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies of the mobility in systems containing conjugated small molecules in an insulating polymer matrix, as a function of the molecule concentration, have revealed values of ␣ −1 around 0.1 nm. 10 The site densities in congated polymers such as OC 1 C 10 -PPV are of the order N t Ϸ 10 26 to 10 27 m −3 , corresponding to average nearest neighbor intersite distances around 1 nm. A representative value of the reduced site density is thus N t / ␣ 3 ϳ 10 −3 .…”
Section: Semianalytical Modelsmentioning
confidence: 99%
“…The mobility can then be expressed as ϰ exp͓−E A / ͑k B T͔͒, with E A an effective activation energy that is of the order of a polaron binding energy. 3,10,11 Further doubts on the applicability of this so-called Gaussian disorder model were raised by the observation that the field-effect ͑hole͒ mobilities in polymer FETs are typically at least one order of magnitude larger than the hole mobility in LEDs based on the same material. Recently, Tanase and co-workers showed that this can be explained as a result of a dependence of the mobility on the hole concentration.…”
Section: Introductionmentioning
confidence: 99%
“…12͒. For organic semiconducting materials, the average intersite distance a = N t −1/3 and the wave-function localization length are typically of the order of 1 and 0.1 nm, respectively, [24][25][26] so that ␣ −1 Ϸ 0.1 ϫ a. The energy levels at neighboring sites are assumed to be uncorrelated.…”
Section: A Mobility and Diffusion Coefficient In A Materials With A Gmentioning
confidence: 99%
“…This form for the mobility has been seen in time of flight measurements on conjugated organic materials, and has been derived theoretically. [13][14][15][16][17][18][19] It has been directly seen in time of flight measurements of MEH-PPV. 20 The device fabrication has been described previously.…”
Section: Introductionmentioning
confidence: 99%